Rapid Short-Read Sequencing and Aneuploidy Detection Using MinION Nanopore Technology. Issue 1 (23rd October 2015) - Wei, Shan; Williams, Zev
Abstract: MinION is a memory stick–sized nanopore-based sequencer designed primarily for single-molecule sequencing of long DNA fragments (>6 kb). We developed a library preparation and data-analysis method to enable rapid real-time sequencing of short DNA fragments (<1 kb) that resulted in the sequencing of 500 reads in 3 min and 40, 000–80, 000 reads in 2–4 hr at a rate of 30 nt/sec. We then demonstrated the clinical applicability of this approach by performing successful aneuploidy detection in prenatal and miscarriage samples with sequencing in <4 hr. This method broadens the application of nanopore-based single-molecule sequencing and makes it a promising and versatile tool for rapid clinical and research applications.